Thalamic Abscess in a Newly Diagnosed Diabetic Patient - Kenneth A. Swanson; Robert J. Citronberg (Case Reports in Infectious Diseases)
Brain abscesses are commonly located in the cerebral cortex and cerebellum; however, solitary thalamic lesions are rare. Recent cases report dental pathology as a common source, potentially compounded by immunocompromise. Here, we report a newly diagnosed diabetic male with poor dentition presenting with evidence of meningitis wherein thalamic abscess was discovered.